2017
DOI: 10.1111/dome.12110
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Effects of Insufficient Support Systems on Kuwaiti Mothers of Children with Disabilities

Abstract: Parents raising a child with a physical or cognitive disability are often faced with the negative stigma against disabilities that exist in several Arab countries. This puts extra pressure on the parents and can lead to negative outcomes for the children. The purpose of this study was to investigate the effects of parenting stress and varying levels of support for mothers of children with disabilities and the effects of these pressures on their relationship with their disabled child. We surveyed 85 Kuwaiti mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…In this study, parental stress was classified according to severity where scores for mild stress ranged between 41 and 59, moderate stress between 60 and 79 and severe stress between 80 and 90. Previous studies conducted in Arab countries such as Kuwait found the translated version of the PSS to be valid and internally consistent (with a Cronbach's alpha between 0.84 and 0.85) (Alsabah & Vittrup, 2017). In the current study, the Cronbach's alpha for the PSS was 0.73.…”
Section: Parental Stress Scalesupporting
confidence: 48%
“…In this study, parental stress was classified according to severity where scores for mild stress ranged between 41 and 59, moderate stress between 60 and 79 and severe stress between 80 and 90. Previous studies conducted in Arab countries such as Kuwait found the translated version of the PSS to be valid and internally consistent (with a Cronbach's alpha between 0.84 and 0.85) (Alsabah & Vittrup, 2017). In the current study, the Cronbach's alpha for the PSS was 0.73.…”
Section: Parental Stress Scalesupporting
confidence: 48%